Antagonistic effects of Lactobacillus plantarum 0612 on the adhesion of selected foodborne enteropathogens in various colonic environments. (September 2018) - Jessie Lau, Li Ying; Chye, Fook Yee
Abstract: The study aims to investigate the antagonistic ability of Lactobacillus plantarum 0612 against foodborne enteropathogens adhesion to the human intestinal Caco-2 cells by competition in a simulated colon model. L. plantarum 0612 has been subjected to the gastrointestinal transits simulation (GITS) prior to assess its competitive inhibition on the adhesion of selected pathogenic strains using intestinal epithelial cells with different colonic pH conditions. Results showed that the adhesion of E. coli and L. monocytogenes on Caco-2 cells was significantly inhibited by L. plantarum 0612 with 4.35 and 4.14 log reductions, respectively. Exclusion and competition mechanisms seemed to be more effective in preventing the colonization of pathogens, indicating L. plantarum 0612 is able to compete for receptors of the epithelial cell surfaces. The GITS tolerance L. plantarum 0612 exhibited stronger competitive inhibition (p < 0.05) on the adhesion of tested pathogens to the Caco-2 cells at lower colonic pH. It was observed that the viable count of E. coli significantly reduced by 5.10 log CFU/ml after 8 h of exposure at colonic pH 5.0. The antagonisms against the adhesion of all selected foodborne enteropathogens in the colonic conditions are probably due to the presence of surface adhesion proteins, which needs further investigation. However, the antagonistic effect of L. plantarum 0612 indicates it could be a promising therapeutic approach for the prevention and management of foodborne diseases. Highlights: Exclusion and competition of L. plantarum 0612 were effective in preventing pathogen colonization. Antagonistic effect of probiotic against adhesion of selected enteropathogens on epithelial cells. Gastrointestinal exposed L. plantarum 0612 showed excellent adhesion inhibition at different colonic pH. The surface adhesion proteins are expected involved in the inhibition that needs further investigation.